IMPROVEMENT OF INVENTORY MANAGEMENT TO REDUCE COST OF BUYING NEW INVENTORY - Warman, Chandra
Natural gas is one of energy from used for various activities such as cooking, production processes, power generation and others. In 2019, natural gas contributed 23% of the national energy mix. This shows that natural gas has an important role in fulfilling national energy. Natural gas is distributed through gas infrastructure, either through pipelines or other modes of transportation, from gas sources to consumers.